Analiza SWOT jako podstawowy element procesu formułowania strategii rozwoju turystyki w województwie zachodniopomorskim - Brelik, Agnieszka (SWOT Analysis as the Key Element of Tourism Development Strategy Creating in the Region Based on an Example of Zachodniopomorskie Province, 2005)
The paper presents an outline strategy of region with special consideration of western Pomeranian region. This strategy will allow development and strengthen regional and local identity and mold social consciousness, economic and ecological to identification people with region and to universals participation in solving problems in molding economics success.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 239-246